Análise multicriterial aplicado na definição de áreas prioritárias ao uso agrícola da terra da bacia do Rio Capivara, Botucatu, SP - Campos, Sérgio [UNESP]; Felipe, Andréa Cardador [UNESP]; Campos, Marcelo [UNESP]; Reche, Aline Minarelli [UNESP] (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2015)
The use of geographic information systems (GIS), combined with advanced analysis technique, enables the standardization and data integration, which are usually from different sources, allowing you to conduct a joint evaluation of the same, providing more efficiency and reliability in the decision-making process to promote the adequacy of land use. This study aimed to analyze the priority areas of the basin agricultural use of the Capivara River, Botucatu, SP, through multicriterial analysis, aiming at conservation of water resources. The results showed that the Geographic Information System Idrisi Selva combined with advanced analysis technique and the weighted linear combination method proved to be an effective tool in the combination of different criteria, allowing the determination of the adequacy of agricultural land use less subjective way. Environmental criteria were shown to be suitable for the combination and multi-criteria analysis, allowing the preparation of the statement of suitability classes for agricultural use and can be useful for regional planning and decision-making by public bodies and environmental agents because the method takes into account the rational use of land and allowing the conservation of hydrics resources.

O uso de sistemas de informação geográfica (SIG), aliado a técnica de análise de multicritérios, possibilita a padronização e a integração de dados, que normalmente são provenientes de diversas fontes, permitindo que se realize uma avaliação conjunta dos mesmos, proporcionando mais eficiência e confiabilidade no processo de tomada de decisão para promover a adequação de uso das terras. Este estudo objetivou analisar as áreas prioritárias ao uso agrícola da bacia do Rio Capivara, Botucatu, SP, por meio da análise multicriterial, visando à conservação dos recursos hídricos. Os resultados mostraram que o Sistema de Informação Geográfica Idrisi Selva aliado à técnica de análise de multicritérios e ao método de combinação linear ponderada mostrou ser uma ferramenta eficiente na combinação dos diferentes critérios, permitindo a determinação da adequação do uso agrícola das terras de forma menos subjetiva. Os critérios ambientais mostraram-se adequados para a combinação e análise multicriterial, permitindo a elaboração do mapa das classes de adequação ao uso agrícola, podendo ser útil para o planejamento regional e nas tomadas de decisões pelos órgãos públicos e agentes ambientais, pois o método leva em consideração o uso da terra racional e permitindo a conservação dos recursos hídricos.
Analysis multicriteria applied in the definition of priority areas for use of agricultural land river basin Capivara, Botucatu, SP
Keywords: Evaluation multicriterial; Soil use; Geographical information system; Avaliação multicriterial; Uso da terra; Sistema de informação geográfica